Diversity and groups - Phillips, Katherine W. (Research on managing groups and teams ;, 2008)
Diversity results from the constellation of individual traits, characteristics, identities, experiences, and knowledge that individuals bring to a group. When individuals come together in groups, the similarities and differences among them may have a profound influence on how they feel, communicate, establish cohesion, deal with conflict, negotiate status differences, share and integrate information, develop ideas, make decisions, process information, and solve problems. The effects of diversity are broad and complex. Although there is a long history of research on diversity, researchers are delving deeper into the moderators, contextual factors, psychological processes, and sociological constraints that impact how individuals and groups manage the complexities of diversity in organizations.This volume will help promote research on diversity in groups by identifying and integrating various areas of research related to diversity across multiple disciplinary traditions. Because researchers in so many different areas have been studying the impact of diversity, and because it plays such an important role in group process and performance, this volume includes chapters and should be relevant for scholars who sit or were trained in many different academic departments including management, communications, psychology, labor and industrial relations and sociology.